Adaptasi Beberapa Varietas Kedelai (Glycine max (L.) Merril) Berdaya Hasil Tinggi Pada Lahan Kering Di Prafi Mulya Sp-1 Manokwari : Pengamatan Terhadap Komponen Pertumbuhan - Benny M. D. Layala; Dwi Wasgito Purnomo; Yohanis Amos Mustamu (Fakultas Pertanian Universitas Papua, 2015)
The purpose of this study was to determine the adaptation of some high yield soybean varieties at dryland area in Prafi Mulya SP-1, Manokwari district. The randomized block design used in this study which consisted of 9 varieaties as the treatment, such as Grobogan, Mutiara, Anjasmoro, Detam-2, Burangrang, Agromulyo, Pangrango,Tanggamus and Local Prafi. The result showed that there was a significant effect ofsoybean varieties to the plant height and branch number.